2001
DOI: 10.1002/eqe.31
|View full text |Cite
|
Sign up to set email alerts
|

Base isolation for near‐fault motions

Abstract: Three analytical studies of base-isolated structures are carried out. First, six pairs of near-fault motions oriented in directions parallel and normal to the fault were considered, and the average of the response spectra of these earthquake records was obtained. This study shows that in addition to pulsetype displacements, these motions contain signiÿcant energy at high frequencies and that the real and pseudo-velocity spectra are quite di erent.The second analysis modelled the response of a model of an isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
189
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(191 citation statements)
references
References 5 publications
0
189
1
1
Order By: Relevance
“…This shows that all the three sliding isolation systems with their recommended parameters undergo almost the same peak displacement under near-fault motion. The corresponding average resultant displacement for a linear isolation system (with a period of 2.5 s and 10% damping) is 53.6 cm that is comparable with the resultant displacement of sliding isolation systems (Jangid and Kelly, 2000). Note that these displacement requirements under near-fault motion are relatively large to accommodate in the isolation system.…”
Section: Near-fault Earthquake Motionmentioning
confidence: 77%
See 1 more Smart Citation
“…This shows that all the three sliding isolation systems with their recommended parameters undergo almost the same peak displacement under near-fault motion. The corresponding average resultant displacement for a linear isolation system (with a period of 2.5 s and 10% damping) is 53.6 cm that is comparable with the resultant displacement of sliding isolation systems (Jangid and Kelly, 2000). Note that these displacement requirements under near-fault motion are relatively large to accommodate in the isolation system.…”
Section: Near-fault Earthquake Motionmentioning
confidence: 77%
“…In the earlier code there were no near-fault factors but in the recent code, near-fault factors have been introduced that make it uneconomic to use isolation in such sites. Recently, there have been several studies for understanding the dynamic behavior of both isolated and fixed base structures under near-fault motion (Markis, 1997;Malhotra, 1999;Jangid and Kelly, 2000). It has been observed that the seismic response of structure under near-fault motion is quite different as compared to the corresponding response with farfault motion.…”
Section: Introductionmentioning
confidence: 99%
“…NF ground motions are characterized by one or more intense long-period velocity and displacement pulses that can lead to a large isolator displacement [2,3]. Therefore, five NF ground motions of different intensities and various velocity and displacement pulses are considered to assess the performance of the RNC isolator damping and buffer mechanisms.…”
Section: Near-fault Ground Motionsmentioning
confidence: 99%
“…However, seismically isolated structures are expected to experience large displacements relative to the ground especially under near-fault (NF) earthquakes. The NF ground motions are characterized by one or more intense long-period velocity and displacement pulses, which lead to a large isolator displacement [2,3]. Such large displacements are accommodated by providing a sufficient seismic gap around the isolated structure.…”
Section: Introductionmentioning
confidence: 99%
“…[3] The pulse displacement is usually associated with the fault-normal direction, where high spectral acceleration components are observed in the long period range. [4] These long period spectral acceleration components tend to resonate with conventionally isolated structures, leading to an excessive base displacement that may destabilize the structure. To maintain the isolation deformations to within acceptable limits, two potential alternatives are to increase the effective stiffness of the isolation system or to provide additional damping mechanisms.…”
Section: Introductionmentioning
confidence: 99%